Nonsynonymous Polymorphism in Guanine Monophosphate Synthetase Is a Risk Factor for Unfavorable Thiopurine Metabolite Ratios in Patients With Inflammatory Bowel Disease. Issue 12 (16th May 2018) - Roberts, Rebecca L; Wallace, Mary C; Seinen, Margien L; van Bodegraven, Adriaan A; Krishnaprasad, Krupa; Jones, Gregory T; van Rij, Andre M; Baird, Angela; Lawrance, Ian C; Prosser, Ruth; Bampton, Peter; Grafton, Rachel; et al.
Abstract: Background: Up to 20% of patients with inflammatory bowel disease (IBD) who are refractory to thiopurine therapy preferentially produce 6-methylmercaptopurine (6-MMP) at the expense of 6-thioguanine nucleotides (6-TGN), resulting in a high 6-MMP:6-TGN ratio (>20). The objective of this study was to evaluate whether genetic variability in guanine monophosphate synthetase ( GMPS ) contributes to preferential 6-MMP metabolizer phenotype. Methods: Exome sequencing was performed in a cohort of IBD patients with 6-MMP:6-TGN ratios of >100 to identify nonsynonymous single nucleotide polymorphisms (nsSNPs). In vitro assays were performed to measure GMPS activity associated with these nsSNPs. Frequency of the nsSNPs was measured in a cohort of 530 Caucasian IBD patients. Results: Two nsSNPs in GMPS (rs747629729, rs61750370) were detected in 11 patients with very high 6-MMP:6-TGN ratios. The 2 nsSNPs were predicted to be damaging by in silico analysis. In vitro assays demonstrated that both nsSNPs resulted in a significant reduction in GMPS activity ( P < 0.05). The SNP rs61750370 was significantly associated with 6-MMP:6-TGN ratios ≥100 (odds ratio, 5.64; 95% confidence interval, 1.01–25.12; P < 0.031) in a subset of 264 Caucasian IBD patients. Conclusions: The GMPS SNP rs61750370 may be a reliable risk factor for extreme 6MMP preferential metabolism.